Growth, dietary intake, and trace element status in pubescent athletes and schoolchildren - Fogelholm, M.; Rankinen, T.; Isokääntä, M.; Kujala, U.; Uusitupa, M. (Medicine & Science in Sports & Exercise, 2000)
To examine interactions between club-level sports training, dietary intake, and nutritional status during puberty. Methods: A 2-yr prospective study was undertaken with 64 boys (40 ice hockey players, 24 controls) and 71 girls (28 gymnasts, figure skaters, and runners, 43 controls). The boys' age in the beginning of the study was 12-13 yr, whereas the girls were 11-12 yr. The following variables were measured in the beginning, and after 1 and 2 yr: physical activity level (record), dietary intake (record), blood hemoglobin concentration, serum ferritin, zinc and copper concentration, anthropometric indices (height, weight, skinfolds, upper arm muscle girth), and biological maturation (self-report). Results and Conclusions: The changes in the anthropometric variables throughout the study period were not different between the athletes and controls (P > 0.09). The athlete boys had higher mean energy, iron and zinc intakes, and higher mean serum zinc concentration than the controls (P < 0.003). The athlete and control girls' dietary intakes and biochemical indices of trace element status were not different from each other (P > 0.13). Moreover, sports participation was not associated with the longitudinal changes in trace element status (P > 0.08). These data suggest that club-level sports training does not affect growth, maturation or nutritional status during puberty.